2020
DOI: 10.1039/d0ra04599c
|View full text |Cite
|
Sign up to set email alerts
|

Luminescent chitosan/carbon dots as an effective nano-drug carrier for neurodegenerative diseases

Abstract: Facile preparation of carbon dots and a chitosan nanocomposite embedded with carbon dots to encapsulate dopamine and ensure biocompatibility and bioavailability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…The cytotoxicity on IC-21 and SH-SY5Y cell lines were found to be about 97 % cell viability proving promising against neurodegenerative diseases. The HR-TEM images, Raman spectra (D, G, 2D bands) confirmed the synthesis of CDs, the particle size was confirmed to be 3 nm through DLS study and the PL property denoted excitation at 510 nm with an emission peak at 550 nm that proved efficient for bioimaging for tracing the drug delivery [ 102 ]. Further, there are many CDs and NCDs (with or without surface modifications), which have successfully encapsulated synthetic as well as natural drug for various drug delivery applications, which are tabulated in Table 3 [ [103] , [104] , [105] , [106] , [107] , [108] ].…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 99%
“…The cytotoxicity on IC-21 and SH-SY5Y cell lines were found to be about 97 % cell viability proving promising against neurodegenerative diseases. The HR-TEM images, Raman spectra (D, G, 2D bands) confirmed the synthesis of CDs, the particle size was confirmed to be 3 nm through DLS study and the PL property denoted excitation at 510 nm with an emission peak at 550 nm that proved efficient for bioimaging for tracing the drug delivery [ 102 ]. Further, there are many CDs and NCDs (with or without surface modifications), which have successfully encapsulated synthetic as well as natural drug for various drug delivery applications, which are tabulated in Table 3 [ [103] , [104] , [105] , [106] , [107] , [108] ].…”
Section: Applications Of Ncds In Drug Deliverymentioning
confidence: 99%
“…A variety of luminescent nanoparticles have been developed and engineered for specific applications of drug imaging and delivery systems 42‐44 . Functionalization of nanomaterials increases significantly its targeting properties and leads to considerable progress in the fundamental understanding, diagnosis, and treatment of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Mathew et al, prepared CDs from chitosan and prepared chitosan/carbon dot‐ based nanocomposite. The result from the study showed that the prepared nanocomposite can be used as a carrier for dopamine for neurodegenerative disease [62] . Chung et al, prepared carbon dots/hydroxyapatite nanocomposite as a drug carrier for acetaminophen.…”
Section: Biomass‐derived Graphene‐based Nanocomposites In Biomedical Applicationsmentioning
confidence: 99%